Optical extinction efficiencies for metallic single wall carbon nanotubes in the infrared spectral region. Issue 4 (4th March 2019) - Alyones, Sharhabeel; Granado, Michael; Bruce, Charles. W.
ABSTRACT: The extinction efficiency (mass normalized extinction cross section) of a sample of metallic single wall carbon nanotubes (SWCNTs) has been measured in the infrared spectral region. The tubes were obtained from Nano-Integris Inc. and measured while suspended in propanol. Calculation of the extinction efficiency based on a computational code for fibers of finite length shows good agreement with the experimental results. The computation involved convolution over the SWCNTs' length and diameter distributions. The results emphasize the potential of SWCNTs as efficient obscurants of electromagnetic radiation in the infrared spectral region.